Middle School Students’ Conceptual Understanding of Diseases: A Learning Progression Approach - Yesika Rahmadani; Murni Ramli; Alanindra Saputra (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2022)
The concept of disease is taught at all levels of schooling in Indonesia, but in non-consecutive core concepts. Such a disjointed approach may affect students’ understanding. Learning progression (LP) is one alternative to sequencing core ideas. This study aims to test the conceptual understanding of disease of 7th and 8th graders, and to check the validity of the LP instrument. The sample (N=296) was selected based on a selected cluster from four middle high schools in Surakarta, Indonesia. The ex post facto design with two unmodified variables, gender and grade, was applied to measure the conceptual understanding of the students. To test this, an Ordered Multiple Choice (OMC) test was conducted. Validity was measured using the Rasch model, and the students’ conceptual understanding was categorised based on four levels of LP. The findings were that the instrument was valid and reliable, but lacked effectiveness in relation to difficulty level and distinguishing power. 38.75% of the students were at level 3, which is the suitable level for both grades, 27.86% were at level 4, and fewer than 20% were at levels 1 and 2. There were no differences in grade and gender. It can be concluded that the number of students with an adequate level of understanding of disease is relatively low. It is therefore recommended that the disease curriculum, as one of the life science topics, is redesigned.